Образы европейцев в книге М. Горького "Жизнь Клима Самгина" - Белова, Тамара; Bielova, Tamara (Східноєвропейський національний університет імені Лесі Українки, 2011)
В статье рассмотрен один из узловых аспектов горьковской концепции жизни – проблема осмысления российской истории, евразийства, «Россия и Европа», воплощенных в итоговой книге писателя в картинах российской и европейской повседневности, в системе образов европейцев начала ХХ века, увиденных глазами заглавного героя. This article is about one of the basic aspect of Gorky’s life conception, namely interpreting the problems of Russian history, «Russia and Europe», realized in writer’s final book according to the pictures of Russian and European reality, system of European images at the beginning of XX century, seen by the main character.
European Images in M. Gorky’s Book «Klim Samgin Life»
Keywords: М. Горький; Самгин; Париж; европейцы; парламент; поэтика; образ; M. Gorky; Samgin; Paris; Europeans; Parliament; poetics; image